2013
DOI: 10.1007/s00266-013-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Skin Defects Without Skin Grafts Using Adipose-Derived Stem Cells

Abstract: A satisfying result is difficult to achieve in the repair of a full-thickness skin defect in the facial area, including the subunits of the nose. A full-thickness skin graft, nasolabial flap, or forehead flap as a major treatment still is used despite its relative potential for secondary contracture, unmatched skin color, hypertrophic scars, and donor-site morbidity. Another option, with good wound-healing power and soft tissue regeneration without skin grafts would be helpful for initiating treatment. Adult s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…In human studies, a phase 1 trial involving ASCs for the treatment of patients with critical limb ischemia showed ulcer improvement and an increase in transcutaneous oxygen [12]. In 2013, ASCs were used for skin defects without skin grafts, and observation showed rapid coverage of wounds with the patient's own regenerated tissue [13]. Furthermore, Reckhenrich et al [14] did a study on the use of an innovative surgical suture filled with ASCs.…”
Section: Introductionmentioning
confidence: 99%
“…In human studies, a phase 1 trial involving ASCs for the treatment of patients with critical limb ischemia showed ulcer improvement and an increase in transcutaneous oxygen [12]. In 2013, ASCs were used for skin defects without skin grafts, and observation showed rapid coverage of wounds with the patient's own regenerated tissue [13]. Furthermore, Reckhenrich et al [14] did a study on the use of an innovative surgical suture filled with ASCs.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, full texts of 54 articles were assessed for eligibility. We excluded 36 studies due to: use of normal lipofilling [17][18][19][20][21][22][23][24] (nine), use in other medical conditions [25][26][27][28][29][30][31] (seven), insufficient outcome data [32,33] (three), use of an artificial material for SVF delivery [34,35] (two), inappropriate design [36][37][38] (three), non-English language [39][40][41] (three), ongoing clinical trial [42,43] (two), and use of predifferentiated cells [44] (one). In four cases [45][46][47][48] full texts were unavailable and in two [49,50] only conference abstracts were accessible.…”
Section: Search Resultsmentioning
confidence: 99%
“…In a study by Gir, Oni, Brown, Mojallal, and Rohrich (2012) 174 published cases of ASC application in clinical settings were analysed, in which no adverse effects were observed. In addition, there are also several clinical studies reporting the acceptable safety and efficacy of application of ASCs in improvement of wound healing (Jeong, 2010;Jo et al, 2013;Karaaltin & Baghaki, 2012;Nambu et al, 2009;Sung et al, 2012). One of the widely used applications of ASCs for wound healing is to improve healing of radiation-caused wounds.…”
Section: Clinical Studies On Improvement Of Wound Healing By Adipose-derived Stem Cellsmentioning
confidence: 99%